MANAJEMEN MUTU DALAM PENGEMBANGAN KOMPETENSI GURU - Mrs Warsiyah (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2016)
AbstractMadrasah Aliyah is an upper secondary educational institutions are characterized by Islam use of the curriculum common and religion. Although many secondary educational institutions such as vocational schools and high schools in the town of Sragen but where Madrash Aliyah in Sragen city can still exist developing and developed. Th is situation is supported by a competence teacher resources and has a high dedication to the development of Madrasah Aliyah. Th is study aims to determine e? orts to develop the competence of teachers in Madrasah Aliyah in Kota Sragen. And also to determine the application of quality management in the development of the teacher competency. Research on teacher competence development and implementation of quality management in the professional development of teachers Madrasah Aliyah uses a qualitative approach, using methods of descriptive analysis. Data collection is done by using the technique of participant observation, interview and documentation. Data form the words, records, reports and documents obtained from the head of the Madrasah, Vice Principals, Teachers and Employees Madrasah Aliyah. Data analysis techniques include data reduction, data presentation, and conclusion. Checking the validity of the data is done by the extension of the presence of the researcher, continuous and careful observation, and triangulation techniques using a variety of sources, methods and theories. From this research note general overview Madrasah Aliyah in Kota Sragen, other forms of competence development of teachers is done, which include: recruitment, education and training, monitoring, supervision and certi? cation of teachers and implementation of quality management through quality planning up to quality control.Keywords: Quality Management, Competence Development of Teachers